Prebiotic, probiotic, and antibiotic growth promoters use in commercial broilers: A comparative study: Gut histology of broilers & growth promoters - Ali, A; Qureshi, AS; Rehan, S; Deeba, F; Usman, M (Journal of the Hellenic Veterinary Medical Society, 2023)
The objective of this study was to observe the effect of Mannan oligosaccharides (MOS), a prebiotic, in the replacement of the antibiotics in the broilers. For this purpose, two hundred broiler chicks were bought from a hatchery and allocated into five treatments having four replicates (10 birds in each). Birds were distributed into five groups; control, antibiotics (Zinc Bacitracin 10%), probiotics (Bacillus subtilis) and prebiotics (MOS), and a combination of probiotics and prebiotics groups. Five iso-nitrogenous and iso-caloric diets were prepared and offered to birds. Feed intake and body weight were recorded. At the end of the trial, birds were slaughtered to obtain carcass and gut health data. Data collected were examined by ANOVA under CRD and mean values were compared using Tukey’s HSD (Honestly significant difference) test. Weight gain was higher (P<0.05) in birds fed diet having probiotics and prebiotics in a combination form. Improved (P<0.05) FCR was recorded in birds fed diet having prebiotics alone and in combination with probiotics. The dressing percentage was higher (P<0.05) in birds fed diet having Probiotics + Prebiotics and control birds. Chest yield was higher (P<0.05) in birds fed having Probiotics + Prebiotics. In gut morphometric parameters, there was observed an increase in villus height, and a significant change of increase in villus surface area was seen. In conclusion, the addition of prebiotics in combination with probiotics, in feed, remarkably improved growth performance and carcass yield in commercial broilers.